Microbiota-driven interleukin-17-producing cells and eosinophils synergize to accelerate multiple myeloma progression. Issue 1 (December 2018) - Calcinotto, Arianna; Brevi, Arianna; Chesi, Marta; Ferrarese, Roberto; Garcia Perez, Laura; Grioni, Matteo; Kumar, Shaji; Garbitt, Victoria; Sharik, Meaghen; Henderson, Kimberly; Tonon, Giovanni; Tomura, Michio; et al.
Abstract The gut microbiota has been causally linked to cancer, yet how intestinal microbes influence progression of extramucosal tumors is poorly understood. Here we provide evidence implying thatPrevotella heparinolytica promotes the differentiation of Th17 cells colonizing the gut and migrating to the bone marrow (BM) of transgenic Vk*MYC mice, where they favor progression of multiple myeloma (MM). Lack of IL-17 in Vk*MYC mice, or disturbance of their microbiome delayed MM appearance. Similarly, in smoldering MM patients, higher levels of BM IL-17 predicted faster disease progression. IL-17 induced STAT3 phosphorylation in murine plasma cells, and activated eosinophils. Treatment of Vk*MYC mice with antibodies blocking IL-17, IL-17RA, and IL-5 reduced BM accumulation of Th17 cells and eosinophils and delayed disease progression. Thus, in Vk*MYC mice, commensal bacteria appear to unleash a paracrine signaling network between adaptive and innate immunity that accelerates progression to MM, and can be targeted by already available therapies. The mechanisms through which gut microbiota affect extramucosal tumors are poorly understood. Here the authors show that the gut microbiota promotes multiple myeloma by inducing differentiation and migration of Th17 cells in the bone marrow resulting also in increased recruitment of pro-tumorigenic eosinophils.